2022
DOI: 10.1111/1751-7915.14170
|View full text |Cite
|
Sign up to set email alerts
|

Marinobacter: A case study in bioelectrochemical chassis evaluation

Abstract: The junction of bioelectrochemical systems and synthetic biology opens the door to many potentially groundbreaking technologies. When developing these possibilities, choosing the correct chassis organism can save a great deal of engineering effort and, indeed, can mean the difference between success and failure. Choosing the correct chassis for a specific application requires a knowledge of the metabolic potential of the candidate organisms, as well as a clear delineation of the traits, required in the applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 133 publications
0
6
0
Order By: Relevance
“…These strains acquired tolerance to these compounds through adjustments made in the phospholipid composition of cell membranes, increased robustness of the protein folding machinery, and a set of efflux pumps that extrude solvents to the external environment from the cytoplasm, periplasm and cell membranes [ 23 ]. In addition to solvent tolerance, a crucial characteristic of microbial chassis for chemical production [ 46 , 47 ] is the ability to maintain the integrity of the desired product(s). In the case of P. putida CM12-5 strain, a phenylalanine producing strain catabolism of the aromatic amino acid is blocked, in addition, the strain does not metabolize t CA and styrene, compounds that can be made from L-phenylalanine [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These strains acquired tolerance to these compounds through adjustments made in the phospholipid composition of cell membranes, increased robustness of the protein folding machinery, and a set of efflux pumps that extrude solvents to the external environment from the cytoplasm, periplasm and cell membranes [ 23 ]. In addition to solvent tolerance, a crucial characteristic of microbial chassis for chemical production [ 46 , 47 ] is the ability to maintain the integrity of the desired product(s). In the case of P. putida CM12-5 strain, a phenylalanine producing strain catabolism of the aromatic amino acid is blocked, in addition, the strain does not metabolize t CA and styrene, compounds that can be made from L-phenylalanine [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…5). Previous studies demonstrated its ability to synthesize various compounds and degrade hydrocarbons in high-salinity environments (37). In addition, Marinobacter were shown to control the formation of bio lms associated with calcium levels(38).…”
Section: Discussionmentioning
confidence: 99%
“…5). Previous studies demonstrated its ability to synthesize various compounds and degrade hydrocarbons in high-salinity environments (47). In addition, Marinobacter were shown to control the formation of biofilms associated with calcium levels (48).…”
Section: Discussionmentioning
confidence: 99%